Identification of tentative antioxidant constituents from stem and leaves of Leea indica species using spectroscopic analysis - Baharom, Fatin Azieyati; Mohd Azam, Naila Nabihah; Harun, Aiza; Daud, Shaari; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian (Universiti Teknologi MARA (UiTM) Cawangan Pahang, 2020)
The tentative antioxidative constituents from stem and leaves extracts of Leea indica which traditionally known as Mali-mali had been investigated. Three different polarities of crude extracts of each part was prepared using consecutive soaking with petroleum ether, dichloromethane and methanol. Screening of antioxidants of each extract on TLC was performed with the use of 2,2 diphenyl-1-picrylhydrazyl (DPPH) as spraying reagent and have been previously reported. The isolation of antioxidative compounds was performed through preparative thin layer chromatography(pTLC) with the use of certain binary solvents system. The structure determination was carried out using Fourier Transform Infra-Red (FTIR), Gas Chromatography Mass Spectrometer (GCMS) and Proton Nuclear Magnetic Resonance (NMR) along with comparison with literature. FTIR analysis depicted some important functional groups such as OH, C-H, C=C and C-O stretching in both parts. The C=O and C-N stretching only appeared in leaves extract of L. indica. According to proton NMR spectrum of leaves part, the chemical shifts belonged to aliphatic protons, vinylic protons, hydroxyl proton and aromatic protons. The proton NMR spectrum of stem part revealed the existence of proton aliphatic, vinylic proton and hydroxyl proton. Based on GCMS analysis with the assistance of Wiley 275.L database matching individually as well as with proton NMR data, the antioxidative compounds isolated from stem part were proposed as 1-(hydroxymethyl)-1,2- ethanediyl ester (LI-1). 9-Oxononanoic acid methyl ester (LI-2), 9,12-Octadecadienoic acid (LI-3), 3’,8,8’-Trimethoxy-3-piperidyl-2,2’-binaphthalene1,1’,4,4’-tetrone (LI-4).